Fraud victimisation of companies: the Cyprus experience - Krambia-Kapardis, Maria (My University, 2002)
Focuses on fraud, including in the concept a wide range of offences committed by management, employees or third parties against the employer/corporation/customer/supplier, and involving the taking of material advantage by deception as a result of which the other suffers financial loss; as in the UK, fraud in Cyprus does not exist as specific criminal offence. Describes fraud as an invisible crime, and lists its negative characteristics: no knowledge, poor statistics, no theory, no research, no political importance, no control, and no moral panic. Estimates the cost of fraud in various societies, including the UK and the USA; in Cyprus, despite the fact that most victim companies had not reported the crime, the estimated losses run into hundreds of millions of Cyprus pounds, and it took the forms of mismanagement of public funds, tax evasion, stolen cheques, bounced cheques, forged cheques, pensioner fraud, share price manipulation, deception and false documentation, pharmaceutical and accountancy fraud. Reports the author’s questionnaire-based research on a sample of Cypriot businesses.
Keywords: Cyprus; Fraud